2016
DOI: 10.1159/000446295
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and Characteristics of Charles Bonnet Syndrome in Turkish Patients with Retinal Disease

Abstract: Purpose: The aim of this study is to investigate the prevalence and clinical characteristics of Charles Bonnet syndrome (CBS) in a group of Turkish patients with various retinal diseases. Methods: Two hundred and sixty-four patients with a best-corrected visual acuity of ≤20/40 in the better-seeing eye were asked with a standardized question whether they had symptoms of CBS. If they responded positively, a questionnaire was verbally administered to learn more about the details of the symptoms. Results: There w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 28 publications
(49 reference statements)
0
6
0
Order By: Relevance
“…Nalcaci et al. () investigated prevalence of CBS in Turkish patients with various retinal diseases and found that CBS was present in 6.4% of patients with AMD. Agron et al.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nalcaci et al. () investigated prevalence of CBS in Turkish patients with various retinal diseases and found that CBS was present in 6.4% of patients with AMD. Agron et al.…”
Section: Resultsmentioning
confidence: 99%
“…Tan et al (2004) were not able to find any cases of CBS in a small sample of 50 patients with AMD. Nalcaci et al (2016) investigated prevalence of CBS in Turkish patients with various retinal diseases and found that CBS was present in 6.4% of patients with AMD. Agron et al (2016) asked participants of CBS in the close-out of the AREDS2 study and found three times higher prevalence of CBS among those with late AMD (9.6% vs. 3.3%).…”
Section: Results Of Individual Studies and Risk Of Bias Within Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Any underlying ocular pathology can precipitate CBS, though literature consistently identifies age-related macular degeneration as a risk factor. [5][6][7] The condition is typically associated with older age; however, the pathogenesis of CBS suggests patients of any age may be affected. 6 8 Typical phenomenology includes transient episodes of simple (ie, shapes and patterns) or complex (ie, life-like scenes, animals and people) hallucinations.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the study, the reported prevalence ranges from 0.4% to 30% among those with sight loss 4. Any underlying ocular pathology can precipitate CBS, though literature consistently identifies age-related macular degeneration as a risk factor 5–7. The condition is typically associated with older age; however, the pathogenesis of CBS suggests patients of any age may be affected 6 8.…”
Section: Introductionmentioning
confidence: 99%